2022
DOI: 10.1002/mnfr.202200134
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Barley Phenolamide by Mice and the Human Gut Microbiota and Quantitative Analysis of the Major Metabolites in Mice

Abstract: Scope: This study investigates the metabolism of p-coumaroylagmatine (pCAA), one of the phenolamides in barley, in mice, and by human gut microbiota, and measures the concentrations of its main metabolites in mice. Methods and results: Nine major metabolites are identified from fecal and urinary samples collected from pCAA treated mice via analysis of their LC chromatograms and tandem mass spectra compared to the commercial and synthesized standards. These nine metabolites are generated through four different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Two barley phenolamides, pCAA and FAA (Figure 1a), were synthesized in-house according to our previous methods. [24] After incubating pCAA, FAA, or metformin with MGO, the percentages of remaining MGO at each time point from each reaction model were measured and shown in Figure 1b. MGO levels in three reaction systems decreased rapidly as incubation time increased.…”
Section: Mgo-trapping Effects By Barley Phenolamidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Two barley phenolamides, pCAA and FAA (Figure 1a), were synthesized in-house according to our previous methods. [24] After incubating pCAA, FAA, or metformin with MGO, the percentages of remaining MGO at each time point from each reaction model were measured and shown in Figure 1b. MGO levels in three reaction systems decreased rapidly as incubation time increased.…”
Section: Mgo-trapping Effects By Barley Phenolamidesmentioning
confidence: 99%
“…Our previous data revealed that pCAA is well absorbed in mice. [24] pCAA can reach up to 2020.44 ± 130.07 μm in mouse urine within 24 h after oral administration of pCAA with a dose of 200 mg kg −1 . [24] In the present study, our results demonstrated that absorbed pCAA and FAA could trap endogenous MGO via the formation of imidazolonetype mono-MGO adducts in mice after oral administration.…”
Section: Scavenging Of Mgo By Barley Phenolamides In Micementioning
confidence: 99%
See 1 more Smart Citation